Employee satisfaction in higher education: a Malaysia case study among non-academic staff / Nurul Ezaili Alias, Mohammad Irfan Hamdani and Rozana Othman - Alias, Nurul Ezaili; Hamdani, Mohammad Irfan; Othman, Rozana (Universiti Teknologi MARA, Cawangan Melaka, 2017)
Many previous studies have solely focused on measuring employee satisfaction among academic staff. However, in a higher educational institution, there are two categories of workforce whom work hard in developing the university; academic and non-academic staff and study on employee satisfaction among non-academic staff still lacking in providing evidence. Hence, it is crucial to study their satisfaction working in the university. This study adapts the research frameworks from previous researches to study the relationship between factors contribute to employee satisfaction and employee satisfaction among non-academic staff. Specifically, the aim of this article is to investigate the relationship between knowledge management, training and leadership and employee satisfaction among non-academic staff at one of public universities in Malaysia. Results of the multiple regression analysis shown that the knowledge management and followed by training are highly affected their overall employee satisfaction, and on the other hand leadership and employee satisfaction shown no significant relationship among non-academic staff. Data analysis of the study has been analyzed using SPSS version 23.